Business ethics : ethical decision making and cases - Ferrell, O. C.; Fraedrich, John.; Ferrell, Linda (Boston : Houghton Mifflin, 2000)
This book is divided into two parts: Understanding Ethical Decision Making; and Cases.
Keywords: Business ethics; Business ethics -- Case studies